2018
DOI: 10.3846/ijspm.2019.6372
|View full text |Cite
|
Sign up to set email alerts
|

Employee Satisfaction With the Physical Work Environment: The Importance of a Need Based Approach

Abstract: Employee satisfaction is pivotal for companies as it enhances perceived productivity and organizational performance. Office concepts and their workspaces can affect employee satisfaction. However, these effects are still ambiguous, particularly regarding the activity-based concept. Therefore, in this study employee satisfaction with the work environment is investigated from a holistic approach. The effects of both personal characteristics and workspaces used by the employee on work environment satisfaction are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 46 publications
(86 reference statements)
6
60
1
1
Order By: Relevance
“…However, the other characteristics found in existing literature (gender, job rank, working hours and current type of workspace, see Table 3) did not significantly distinguish the different segments here. Budie, Appel-Meulenbroek, Kemperman, and Weijs-Perree (2018) already stated that there is little evidence of whether and how the current workspace might influence preferences, and the findings here show no proof of this either. But for example, Al Horr et al (2016) found that females dislike open office environments more, which could not be confirmed here.…”
Section: Discussioncontrasting
confidence: 88%
“…However, the other characteristics found in existing literature (gender, job rank, working hours and current type of workspace, see Table 3) did not significantly distinguish the different segments here. Budie, Appel-Meulenbroek, Kemperman, and Weijs-Perree (2018) already stated that there is little evidence of whether and how the current workspace might influence preferences, and the findings here show no proof of this either. But for example, Al Horr et al (2016) found that females dislike open office environments more, which could not be confirmed here.…”
Section: Discussioncontrasting
confidence: 88%
“…In line with our study's findings, the impact of HPWS on employee job satisfaction (Heffernan & Dundon, 2016;Kloutsiniotis & Mihail, 2017;Mahmood et al, 2019) as well as the impact of job satisfaction on organizational performance (Budie et al, 2019;Delaney & Huselid, 1996;Schyns & Croon, 2006) has been confirmed in several studies.…”
Section: Discussion and Comparisonsupporting
confidence: 91%
“…First of all, we posit that the quality of lactation rooms may influence women’s overall satisfaction with these rooms. Satisfaction with the physical environment relates to the extent to which the physical environment meets individuals’ physiological, functional, and psychological needs [ 24 , 25 ]. Accordingly, it can be assumed that the extent to which a lactation room meets the needs of the mothers using it, determines their satisfaction with the room.…”
Section: Introductionmentioning
confidence: 99%